Investor Trading Patterns And Performance Before, During And After Two Consecutive Crises: Evidence From Egyptian Stock Market - Abdalla, Mohamed Ahmed Elsayed Sleem (2019)
Egypt was shocked by the 2007/2008 global financial crisis, and was hit strongly by the 2011 domestic political crisis. Despite the fact that EGX is a promising active emerging stock market, the background of EGX illustrated by Niemczak & Smith (2013) shows that EGX is not only inefficient but also fragile and exposed to crisis. Therefore, it is expected that some investors are more informed and it is worth to investigate such case in light of the two recent crises particularly the political turmoil. Using behavioral finance aspects, this research aims to identify the trading patterns (e.g. momentum, contrarian) and performance of buy and sell trades conducted by different types of investors (i.e., domestic individuals, domestic institutions, foreign individuals, and foreign institutions) during crisis and non-crisis periods. The dataset of investors’ daily inflows and outflows is extended from January 2006 to December 2016. The Vector Autoregressive (VAR) is employed to detect feedback trading, and volatility (e.g. via Wald test), while the method of Kamesaka et al. (2003) is employed to measure the performance of each investor category. The results indicate that the trading strategies utilized by the four investor categories during crisis periods differ from those employed during non-crisis periods. Second, momentum and contrarian patterns are heavily employed but in different intense. Further, Institutional foreigners were winners during the five sub-periods while Individual investors were nearly always losers. This suggests that foreign institutions are information-driven while individuals are behavioral-driven as in Kamesaka et al. (2003).